THE FREE ALPHA AMINO NITROGEN CONTENTS OF SOME COMMON FOOD FISHES OF KAKINADA REGION , ANDRAPRADESH - GUPTA, SIBSANKAR; GOVINDAN, T K (Fishery Technology, 2017)
The moisture and free alpha amino nitrogen contents of some important food fishes and sheH fishes of Kakinada region have been studied. Crustacearis and molluscs contain free alpha amino acids in quantities several times higher than all other aquatic animals examined in this study. Their probable role in the physiological activities of these animals has been discussed